Beyond Borders: Personal Stories from a Small Planet - Haeberle, Austin (Haeberle, Austin, 2005)
Verzio FF submission A creative project made by teenagers overcoming huge obstacles and ignorance within their lives. A compilation of 11 short films written, shot and edited by teenagers who weave documentary filmmaking, animation and archival footage to tell personla stories about what they most fear and how they build security to overcome those fears.